2005
DOI: 10.1681/asn.2004040287
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Excretion of β2-Microglobulin and IgG Predict Prognosis in Idiopathic Membranous Nephropathy

Abstract: An accurate prediction of the prognosis of patients with idiopathic membranous nephropathy (iMN) should allow restriction of immunosuppressive treatment to patients who are at highest risk for ESRD. On the basis of retrospective studies, it has previously been suggested that the urinary excretions of ␤2-microglobulin (U␤2m) and IgG (UIgG) are useful predictors of renal insufficiency in patients with iMN. The threshold values of 0.5 g/min (U␤2m) and 250 mg/24 h (UIgG) have been validated in a new and larger pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
2
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 19 publications
1
79
2
3
Order By: Relevance
“…There is ongoing research into whether additional factors, such as urinary biomarkers, may help predict the course of the disease and/or who will respond to therapy. Several authors have examined whether the measurement of low and high molecular weight urinary proteins may be helpful in determining prognosis, rate of progression and response to therapy in membranous nephropathy [72], [73], [74] and [75]. Bazzi et al [76] published a study in 2001 looking at the excretion of urinary proteins in 78 patients with membranous nephropathy.…”
Section: Idiopathic Membranous Nephropathymentioning
confidence: 99%
“…There is ongoing research into whether additional factors, such as urinary biomarkers, may help predict the course of the disease and/or who will respond to therapy. Several authors have examined whether the measurement of low and high molecular weight urinary proteins may be helpful in determining prognosis, rate of progression and response to therapy in membranous nephropathy [72], [73], [74] and [75]. Bazzi et al [76] published a study in 2001 looking at the excretion of urinary proteins in 78 patients with membranous nephropathy.…”
Section: Idiopathic Membranous Nephropathymentioning
confidence: 99%
“…Recently, it has become possible to measure markers in urine samples that represent damage to different parts of the nephron (12). These damage markers initially drew much attention as possible early predictors of AKI, but have also recently been reported as predictors for progressive CKD (13)(14)(15)(16). In these studies, progressive CKD was defined as loss of GFR.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, urinary markers have been suggested to predict progression in iMN (5)(6)(7)(8)(9). We showed that urinary excretion of b2-microglobulin (ub2m) or a1-microglobulin (ua1m) accurately predicted progressive loss of kidney function (10,11). When re-evaluated, both markers showed somewhat lower sensitivity and specificity than before.…”
Section: Introductionmentioning
confidence: 90%
“…Immunosuppressive therapy was advised only in patients with evidence of deteriorating kidney function or severe untreatable nephrotic syndrome. Data of 46 patients were also used in our previous study of low-molecular weight proteins (10).…”
Section: Populationmentioning
confidence: 99%
See 1 more Smart Citation